Equity Risk Factors for the Long and Short Run: Pricing and Performance at Different Frequencies - Terri van der Zwan; Erik Hennink; Patrick Tuijp (Tinbergen Institute, 2021)
We find that the outperformance for Fama-French factors compared to macroeconomic factors in terms of fitting the cross-section of expected returns disappears when accounting for horizon effects. In addition, we obtain novel empirical relations between macroeconomic factors and Fama-French factors at longer horizons. To obtain our results, we introduce a general linear multifactor asset pricing methodology that integrates systematic risk measured at different frequencies into a single pricing equation. Our setup allows for a setting where investors with different investment horizons may experience different levels of systematic risk, which could arise from delayed stock price reaction to systematic factor news.
Keywords: G12; C58; G11; 330; Cross-Section of Stock Returns; Factors; Frequency Decomposition; Horizon Effects; Investment Horizon